2017
DOI: 10.1111/aos.13545
|View full text |Cite
|
Sign up to set email alerts
|

Automated refraction is stable 1 week after uncomplicated cataract surgery

Abstract: Automated refraction is stabile 1 week after uncomplicated cataract surgery, but there is a trend towards instability, if the refractive target is missed with 1.0 D or more.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 12 publications
(29 reference statements)
1
23
0
Order By: Relevance
“…In our study population, the spherical equivalent was already stable on the second post- [2,5,8]. Thus, our results suggest that the spherical equivalent stabilises sooner after uneventful cataract surgery than previously reported in many patients.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…In our study population, the spherical equivalent was already stable on the second post- [2,5,8]. Thus, our results suggest that the spherical equivalent stabilises sooner after uneventful cataract surgery than previously reported in many patients.…”
Section: Discussionsupporting
confidence: 68%
“…There is no international consensus about the optimal timing to prescribe spectacles after cataract surgery. In Denmark, typical clinical practice suggests postponing new spectacles for at least 4 weeks, but is dependent on the clinician’s discretion [ 2 ]. In the past decade, progress has been made in cataract operation techniques and equipment.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the substantial change in refraction and the resulting variation of accommodative demand, the bibliographic references regarding accommodation or binocularity status in highly ametropic patients implanted with phakic IOLs are scarce, but some authors reported that sphere‐ and spherical‐equivalent‐stability was achieved 1 month after surgery (Ostri et al. ).…”
Section: Resultsmentioning
confidence: 99%
“…They concluded spectacles could be prescribed 2-weeks following uneventful cataract surgery. The remaining three studies 27,28,32 concluded refraction was stable after 1-week. De Juan grouped together mean and SD using data from both eyes of most patients, 22 without correction for the lack of independence of right and left eye data.…”
Section: Potentials For Biasmentioning
confidence: 99%
“…Few discussed how many patients were excluded due to the tight inclusion and exclusion criteria. 28,30,32 This information is critical to know how applicable the findings are to the general population. How and who measured refraction has the potential to bias the study endpoint.…”
Section: Potentials For Biasmentioning
confidence: 99%